Peningkatan Pengetahuan Cuci Tangan Pakai Sabun pada Anak Sekolah Dasar di SDN 060831 Kota Medan - Annisa Febriana Siregar; Tifani Hadi Tri Wahyuni; Annisatun Munawaroh; Siska Tri D Lase; Nucholisah Fitra (STIKES Columbia Asia Medan, 2025)
Washing hands with soap is one of the preventive measures to protect against contagious diseases, especially in children. This study aims to increase students' knowledge about the correct handwashing technique through counseling at SDN 060831. The method used includes counseling sessions with pre-tests and post-tests to assess changes in participants' knowledge. The results show a significant increase in participants' knowledge, with the average pre-test score being 80.3, which increased to 94.1 in the post-test. The activity involved 25 students, consisting of 15 female students and 10 male students. This counseling successfully enhanced students' understanding of the importance of washing hands with soap, which is expected to be applied in their daily lives to support a healthy lifestyle.